Aggregate Size Dependence of Amyloid Adsorption onto Charged Interfaces - Tesei, Giulio; Hellstrand, Erik; Sanagavarapu, Kalyani; Linse, Sara; Sparr, Emma; Vácha, Robert; Lund, Mikael (Langmuir, 2018)
Amyloid aggregates are associated with a range of human neurodegenerative disorders, and it has been shown that neurotoxicity is dependent on aggregate size. Combining molecular simulation with analytical theory, a predictive model is proposed for the adsorption of amyloid aggregates onto oppositely charged surfaces, where the interaction is governed by an interplay between electrostatic attraction and entropic repulsion. Predictions are experimentally validated against quartz crystal microbalance-dissipation experiments of amyloid beta peptides and fragmented fibrils in the presence of a supported lipid bilayer. Assuming amyloids as rigid, elongated particles, we observe nonmonotonic trends for the extent of adsorption with respect to aggregate size and preferential adsorption of smaller aggregates over larger ones. Our findings describe a general phenomenon with implications for stiff polyions and rodlike particles that are electrostatically attracted to a surface.
Keywords: amyloidní beta-protein; Quartz Crystal Microbalance Techniques; Amyloid; adsorpce; Surface Properties; amyloid; povrchové vlastnosti; Amyloid beta-Peptides; mikrorovnovážné techniky křemenného krystalu; Adsorption